Silencing of IL13RA2 promotes partial epithelial‐mesenchymal transition in hepatocellular carcinoma via ERK signaling pathway activation. Issue 2 (10th January 2020) - Wang, Mimi; Yao, Rongrong; Wang, Yanhong
Abstract : Lack of insight into the mechanisms underlying hepatocellular carcinoma (HCC) metastasis has hindered the development of curative treatments. Overexpression of interleukin‐13 receptor alpha 2 (IL13RA2) has been reported to contribute to invasion and metastasis in several tumors. However, the role of IL13RA2 in HCC remains to be characterized. In this study, we identified that low expression of IL13RA2 is associated with poor survival of patients with HCC, and demonstrated that IL13RA2 knockdown endows HCC cells with invasive potential. Mechanistically, silencing of IL13RA2 promotes partial epithelial‐mesenchymal transition via increasing extracellular signal‐regulated kinase phosphorylation in HCC. Collectively, our results suggest that IL13RA2 may have potential as a prognostic biomarker for HCC. Abstract : Expression of interleukin‐13 receptor alpha 2 (IL13RA2), one of the receptors for interleukin‐13, is low in hepatocellular carcinoma (HCC) compared with normal hepatic tissue. Silencing of IL13RA2 promoted tumor cell migration via intrinsic phosphorylation of extracellular signal‐regulated kinase, and The Cancer Genome Atlas analysis suggests that IL13RA2 may be a potential prognostic biomarker of long‐term survival for patients with HCC.